Avaliação de inibidores voláteis de corrosão por técnicas eletroquímicas sobre o aço - Valente Junior, Marco Antonio Gomes [UNESP] (2014)
In this work, the efficiency of volatile corrosion inhibitors (VCI), applied to the protection against corrosion of CFF steel, was studied. In order to evaluate the inhibitors, it was determined the polarization resistances and some kinetic parameters by using the following electrochemical techniques: cyclic polarization curves, electrochemical impedance spectroscopy (EIS), and linear polarization. In addition, it was investigated the influence of cathodic overpotential on the polarization curves and the effect of pH close to the electrode surface on the kinetic parameters. The latter was conducted by means of simultaneous measurements of the pH values employing a W/WOx electrode. The evaluated inhibitors were: ethanolamine (ETA), cyclohexylamine (CHA), dicyclohexylamine (DCHA), caprylic acid (H-CAP), sodium caprylate (Na-CAP), ethanolamine caprylate (ETA-CAP), cyclohexylamine caprylate (CHA-CAP), dicyclohexylamine caprylate (DCHA-CAP). These inhibitors were dissolved and studied in the following solutions: a) 0.1 mol L-1 NaCl and b) borate buffer (BB) + 0.1 NaCl mol L-1. The obtained results showed that the parameters of Tafel curves depend on the cathodic overpotential applied in the beginning of the polarization curves. These parameters alter the pH on the electrode surface due to the oxygen reduction and water reactions which produce hydroxyls ions besides removing the oxides film. It was noticed that these effects are minimized when a buffer solution is employed. The inhibitors efficiency does not show a significant variation with respect to the different used electrochemical techniques. However, the inhibitors efficiency varies as a function of the used solution pH (0.1 mol L-1 NaCl or BB + 0.1 NaCl mol L-1) showing that the protonated amines were not efficient while the unprotonated amines passivate the electrode surface owing to an increase in the solution pH (> 11.7). The amines caprylates were efficient on both NaCl and BB...